Self-Stabilization of Grid-Connected Inverters by Means of an Impedance-Based Adaptive Controller - Joel Filipe Guerreiro; Tiago Davi Curi Busarello; Hildo Guillardi; Igor Alves Maronni; Jose De A. Olimpio Filho; Helmo K. Morales Paredes; Jose A. Pomilio (IEEE Open Journal of Industry Applications, 2025)
The grid-connected inverter is responsible for exchanging energy between the electrical grid and energy sources, such as photovoltaic and storage. The interconnection stability of these inverters may be addressed via their impedance characteristics, which comprise the control system and the ac filter. In many cases, the stability deteriorates when these devices are placed in weak grids due to the known effects of phase-locked loop and voltage feedforward. LCL-type ac filters and resonant-based controllers also pose challenges to the stability of the operation. This work proposes an approach to impedance shaping to stabilize LCL-type grid-connected inverters in nonideal grids with long feeders and disturbing loads. The method relies on regulating the voltage feedforward gain by disturbing and adapting the system based on the distortion of the output current. The technique enables the self-stabilization of the inverter even when an instability is already triggered and without the need for impedance measurements or processor-intensive algorithms. A frequency sweep verification is performed to measure the converter’s impedance and validate it against the theoretical one. An hardware experiment is implemented to evaluate the stability of the converter for large grid impedance variations using the proposed impedance shaping approach.